Peripherally Donor-Installed 7,8-Diaza[5]helicenes as a Platform for Helical Luminophores - Ikari, Yuta; Kaihara, Takahito; Goto, Shimpei; Bovenkerk, Marcel; Grenz, David C.; Esser, Birgit; Ferreira, Marli; Stachelek, Patrycja; Data, Przemyslaw; Yoshida, Takumu; Ikai, Tomoyuki; Tohnai, Norimitsu; Minakata, Satoshi; Takeda, Youhei (Synthesis, 2021)
A new family of emissive donor–acceptor–donor (D-A-D) compounds has been developed by introducing two electron donors into the 7,8-diaza[5]helicene core as a novel helical electron acceptor. The X-ray crystallographic analyses revealed the uniquely twisted and helical structures of these compounds in the solid states. Notably, some D-A-D compounds developed herein display distinct mechanochromic luminescence (MCL) in the solid state, and a D-A-D helicene shows circularly polarized luminescence (CPL) with a relatively high luminescence dissymmetry factor glum of ca. 10–3. Time-resolved spectroscopic analysis revealed the aspects of thermally activated delayed fluorescence characters of the helicenes. Furthermore, the emissive helicenes were applied to organic light-emitting diodes as emitters.
Keywords: helical structures; mechanochromism; circularly polarized luminescence; donor-acceptor; charge-transfer; organic light-emitting diodes; amination